Fatal systemic adenoviral infection superimposed on pulmonary mucormycosis in a child with acute leukemia: A case report. Issue 40 (October 2016) - Seo, Yu Mi; Hwang-Bo, Seok; Kim, Seong koo; Han, Seung Beom; Chung, Nack-Gyun; Kang, Jin Han
Abstract: Background: Although adenovirus (ADV) infection usually causes self-limiting respiratory disorders in immune competent children; severe and systemic ADV infection in children undergoing chemotherapy for leukemia has been continuously reported. Nevertheless, there has been no consensus on risk factors and treatment strategies for severe ADV infection in children undergoing chemotherapy. Case summary: We report a case of a 15-year-old boy with a fatal systemic ADV infection. He had received reinduction chemotherapy for relapsed acute lymphoblastic leukemia under continuing antifungal therapy for previously diagnosed fungal pneumonia. He complained of fever and right shoulder pain 4 days after completing the reinduction chemotherapy. In spite of appropriate antibiotic and antifungal therapy, pneumonia was aggravated and gross hematuria was accompanied. A multiplex polymerase chain reaction test for respiratory viruses was positive for ADV in a blood sample, and a urine culture was positive for ADV. He received oral ribavirin, intravenous immunoglobulin, and intravenous cidofovir therapy; however, he eventually died. Relapsed leukemia, concurrent fungal pneumonia, and delayed cidofovir administration were considered the cause of the grave outcome in this patient. Conclusion: ADV may cause severe infections not only in allogeneic hematopoietic cell transplant recipients, but also in patients undergoing chemotherapy for acute leukemia. The risk factors for severe ADV infection in patients undergoing chemotherapy should be determined in the future studies, and early antiviral therapy should be administered to immune compromised patients with systemic ADV infection.